Study on the Function and Mechanism of miR-585-3p Inhibiting the Progression of Ovarian Cancer Cells by Targeting FSCN1 to Block the MAPK Signaling Pathway - Yiming Jia; Jingru Li; Jinfeng Wang; Tianjiao Luo; Xiaoqian Jing; Hongmin Zhao (Analytical Cellular Pathology)
Ovarian cancer (OC) is the leading cause of death for women diagnosed with gynecological cancer. Studies have shown that dysregulated miRNA expression is related to various cancers, including OC. Here, we aimed to explore the biological function and mechanism of miR-585-3p in the occurrence and development of OC. The expression level of miR-585-3p was found to be low in OC tissues and cells. We analyzed the biological function of miR-585-3p in OC through in vitro cell experiments. The results indicated that overexpression of miR-585-3p inhibited the proliferation, invasion, and migration of SW626 cells, while low expression of miR-585-3p had the opposite effect in SKOV3 cells. We then screened the target genes of miR-585-3p through miRDB database and detected the expression of target genes in OC cells. FSCN1 was found to be most significantly upregulated in OC cells. Dual-luciferase reporter assays revealed FSCN1 as a potential target of miR-585-3p. Western blot analysis showed that miR-585-3p targeted FSCN1 to inhibit protein phosphorylation of ERK. In vivo animal experiments also confirmed that miR-585-3p targets FSCN1 to inhibit tumor growth and block the MAPK signaling pathway. In summary, miR-585-3p inhibits the proliferation, migration, and invasion of OC cells by targeting FSCN1, and its mechanism of action may be achieved by inhibiting the activation of the MAPK signaling pathway. miR-585-3p may serve as a potential biomarker and therapeutic target for OC.